Radiostratigraphy Reflects the Present-Day, Internal Ice Flow Field in the Ablation Zone of Western Greenland - Florentine, Caitlyn; Harper, Joel; Johnson, Jesse; Meierbachtol, Toby (Frontiers in Earth Science, 2018)
Englacial radar reflectors in the ablation zone of the Greenland Ice Sheet are derived from layering deposited in the accumulation zone over past millennia. The original layer structure is distorted by ice flow toward the margin. In a simplified case, shear and normal strain incurred between the ice divide and terminus should align depositional layers such that they closely approximate particle paths through the ablation zone where horizontal motion dominates. It is unclear, however, if this relationship holds in western Greenland where complex bed topography, three dimensional ice flow, and historical changes to ice sheet mass and geometry since layer deposition may promote a misalignment between present-day layer orientation and the modern ice flow field. We investigate this problem using a suite of analyses that leverage ice sheet models and observational datasets. Our findings suggest that across a study sector of western Greenland, the radiostratigraphy of the ablation zone is closely aligned with englacial particle paths, and is not far departed from a state of balance. The englacial radiostratigraphy thus provides insight into the modern, local, internal flow field, and may serve to further constrain ice sheet models that simulate ice dynamics in this region.